State Cash Resources and State Building in Europe 13th-18th century - Katia Béguin (Institut de la gestion publique et du développement économique, 2017)
In July 2012 historians and economists met in Paris for a conference entitled State Cash Resources and State Building in Europe: taxation and public debt, 13th-18th centuries. This volume is one of the products of that meeting. By making these essays available in both French and English translations, the editors hope to ensure a wide audience for an important set of contributions on questions relating to the development and management of public finance and its connection with the growth and power of the early modern state. Contributors were asked to consider three major themes in their essays: first, the choices that faced states seeking to raise funds and, in particular, questions of how to balance taxation and borrowing. Second, contributors were asked to explore the connections between political regime and finance. This included the much-explored question of whether particular regimes were more effective at raising funds and were viewed as more reliable borrowers but the essays also ask how the rights of creditors were enforced and how creditors monitored those to whom they lent money. The final theme concerned the primary and secondary markets in state debt and here the contributors focused on questions of liquidity, transparency and the skills of those who traded and manipulated the instruments of the state's debt. The resulting essays offer a comparative perspective over six centuries of European history. Taken together they provide a rich new resource and challenge both the neat dichotomies that have been drawn between absolutist and constitutional states and entrenched ideas about how practice evolved and knowledge and skills were shared and transferred between actors and states.